Spiritual and Educational Policy of the Samanid State - Tojievich, Juraev Bobomurod (Journal of Innovation in Education and Social Research, 2024)
The article tells about the libraries of the Samanid state, which were the center of culture and spirituality. It is shown how the libraries of that period widely disseminated science, spirituality and art, were the center of the development of spiritual and educational culture. The purpose of this study is to determine the place of books and libraries in the history of the cultural tradition of the Samanid state. In this regard, the following tasks are defined: to identify the relationship and influence of socio-political conditions on the formation and development of librarianship and to determine the role of the book in the educational processes of the Samanid era; highlight the place and role of books and libraries in the era of the Samanids; to reveal the factors of the increase in the number of libraries in the era of the Samanids; determine the role of kings, viziers, sages, cultural and political figures of the Samanid society in the growth of the number of libraries; establish the place of libraries in the creation of scientific and cultural movements in the era of the Samanids.